Study of the spectral characters–chlorophyll inversion model of Sabina vulgaris in the Mu Us Sandy Land - Wang, Ning; Yang, Guang; Han, Xueying; Jia, Guangpu; Li, Qinghe; Liu, Feng; Liu, Xin; Chen, Haoyu; Guo, Xinyu; Zhang, Tianqi (Frontiers in Earth Science, 2023)
Sabina vulgaris is a group tree species in Mu Us Sandy Land. Understanding the growth status of Sabina vulgaris has guiding value for vegetation change monitoring. Chlorophyll is an important indicator to characterize the growth status of plants, and its content changes are important for analyzing the physiological growth status of plants and guiding the precise planting of plants. In this paper, the spectral reflectance and chlorophyll content of Sabina vulgaris were measured by SVC HR-1024 portable ground feature spectrometer and SPAD502 chlorophyll instrument, and the relationship between ground feature spectral characteristics and chlorophyll content of Sabina vulgaris was studied. The results show that there is a correlation between the vegetation index and chlorophyll, the effect of NDVI is the best, the bands with the highest correlation are the combined bands of 470nm-500nm, 610nm-680nm, and 740nm-840nm, and the wavelengths with the highest correlation are (660,790); Vegetation index, red-edge parameters, and chlorophyll have a certain correlation. The fitting effect of the model established by vegetation index is better than that established by red-edge parameters, and the highest R2 is 0.97; Among the three modeling methods, the model fitting effect of partial least squares is the best, R2 is > 0.91, and the disadvantage is that the processing process is complex; The processing method of the univariate linear regression model is the simplest, but the disadvantage is that the accuracy of the model is unstable, R2 is between 0.1-0.9, so the multivariate linear regression model is the most suitable of the three methods(R2>0.8).